KESIAPSIAGAAN PT PELINDO II LAMPUNG DALAM MENGHADAPI ANCAMAN TSUNAMI DI PROVINSI LAMPUNG - Miftah Ali; Syamsul Maarif; Sobar Sutisna (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This study aims to analyze the preparedness of PT Pelindo II Lampung in facing the tsunami threat in Lampung Province. The research method used in this research is a qualitative method with a descriptive approach and data interview techniques using interviews, observation, and documentation. The results showed that (1) PT Pelindo II has a preparedness plan in facing the threat of earthquake and tsunami disasters, (2) PT Pelindo II has prepared evacuation routes for employees when a disaster occurs in all office locations, (3) PT Pelindo II has provided a place alternatives for loading and unloading activities during a disaster, (4) PT Pelindo has stipulated ship and goods insurance in the PT Pelindo II area when a disaster occurs, and (5) PT Pelindo II has implemented disaster rules on performance by having Business Continuity Management (BCM) based on small to large disasters.